Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/oir-08-2019-0262
|View full text |Cite
|
Sign up to set email alerts
|

Digital media users and Facebook hashtags' misinterpretations

Abstract: PurposeThis paper examines reasons of pragmatic functions' misinterpretation of three types of Facebook hashtags: long, short and multiple mixed hashtags.Design/methodology/approachFocus group interviews of 15 English language learners, who are also active users of Facebook and hashtags, are conducted. Thematic analysis is performed through the software Nvivo for arriving at reliable findings.FindingsThe findings show that unknown vocabulary in contents and lowercasing in long and short hashtags are major fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This study concludes that lower casing in writing style, lack of knowledge and inadequate vocabulary create misinterpretation among English language learners in Pakistan. Results of the study confirmed that the use of Facebook is limited to informal language learning where hashtags are used to add style (Tariq and Sarfraz, 2018) in social media posts while attaining language learning benefits are far behind.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…This study concludes that lower casing in writing style, lack of knowledge and inadequate vocabulary create misinterpretation among English language learners in Pakistan. Results of the study confirmed that the use of Facebook is limited to informal language learning where hashtags are used to add style (Tariq and Sarfraz, 2018) in social media posts while attaining language learning benefits are far behind.…”
Section: Discussionmentioning
confidence: 65%
“…The present study explores that several language factors such as abbreviation, acronym, capitalization, case sensitivity (lower and upper casing of letters), symbol of underscore, different languages complete words, alteration between two or more languages (code-switching), and digits are used in three types of hashtags on Facebook as highlighted by Tariq et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations